(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Since ancient times, in Karakalpaks , there were different types of transportation tools , due to the diversity of families. People engaged in agriculture often used carts, while those engaged in fishing used boats, sledges, and rafts.